Mathematical Analysis of a Generalized Chiral Quark Soliton Model - Arai, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
A generalized version of the so-called chiral quark soliton model (CQSM) in nuclear physics is introduced. The Hamiltonian of the generalized CQSM is given by a Dirac type operator with a mass term being an operator-valued function. Some mathematically rigorous results on the model are reported. The subjects included are: (i) supersymmetric structure; (ii) spectral properties; (iii) symmetry reduction; (iv) a unitarily equivalent model.